Development of diving capacity and behaviour in harp seal (Pagophilus groenlandicus) weanlings from the Greenland Sea Stock - Malde, Aleksander (UiT Norges arktiske universitet, 2019)
This study represents one of the first studies that has explored the spatial and temporal differences in diving behaviour of weaned harp seal pups (Pagophilus groenlandicus) from the Greenland Sea stock. The study is also the first to map the weaned harp seal pups from the Greenland Sea population. In April 2017, newly weaned harp seal pups (n=26) from the Greenland Sea stock were tagged with satellite linked dive recorders. The dives and the movement of the pups were recorded and were then relayed. After release, the pups quickly began to dive and reached a diving performance of 4.27 (SD = 0.61) minutes after just 29.44 (SD = 22.00) days. This quick increase of diving performance is probably the result of dive training, increasing the myoglobin stores due to hypoxia and activity. Later in the study, the diving performance stabilised at about ~6 minutes, this is more due to external factors. The pups mostly dived shallow, but one seal had a dive to the depth of 600 meters. The harp seal pups followed the pack-ice north-east into the Barents Sea over the winter and comes back to the Greenland Sea in the end of April 2018, corresponding to the moulting. They mostly followed the distribution of the adults from the Greenland Sea stock, but most pups did not go into the Denmark Strait before the whelping period in the end of March. Foraging focal areas were by the ice-edge in the Northern Barents Sea, Svalbard Bank and around Bjørnøya.